GASTROPODS (MOLLUSCS) IN MANGROVE ECOSYSTEM AT CINGAM VILLAGE, RUPAT SUBDISTRICT, BENGKALIS REGENCY - Noel GM Situmorang; Syafruddin Nasution; Efriyeldi Efriyeldi (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
Abstract             The gastropods play an important role as bioindicators of environmental quality due to its living habits is relatively sedentary in one area for a long period and pass the impact of environmental changing. This research aims to recognise types, abundance, distribution of gastropods and the relationship organic content of sediment to the gastropods abundance. This research was held atn November 2017 in mangrove ecosystem Sungai Cingam Village, Rupat Subdistrict, Bengkalis Regency. The method used was survey method, meanwhile the determination of research points were measured by purposive sampling method. The research area was devided into 3 (three) stations where each station consists of 3 (three) transects. Each transect has 3 (three) plots measuring 3m x 3m. The results of research on mangrove ecosystem of Cingam River Village found 18 species of gastropods. Abundance of gastropods ranged from 13.44 to 16.19 individuals / m² with the highest abundance found in Station II with good mangrove forest condition Grouping is distribution formula of gastropods in mangrove ecosystem at Cingam Village. Organic content of sediment is around 6.96% to 8.98%.The highest organic content in Station II and the lowest in station III. The result of simple regression test obtained the equation y = 5.2158 + 1.2555x with correlation value (r) = 0.812 indicates strong connection between organic content of sediment and abundance of gastropods. Keywords : Abundance, Gastropods, Mangrove Ecosystem, Bengkalis